Functional Integration of Adult-Generated Neurons in Diabetic Goto-Kakizaki Rats - Damphousse, Chelsey C.; Medeiros, Jaclyn; Marrone, Diano F. (Frontiers in Behavioral Neuroscience, 2021)
Adult-born neurons in the dentate gyrus (DG) make important contributions to learning as they integrate into neuronal networks. Neurogenesis is dramatically reduced by a number of conditions associated with cognitive impairment, including type 2 diabetes mellitus (T2DM). Increasing neurogenesis may thus provide a therapeutic target for ameliorating diabetes-associated cognitive impairments, but only if new neurons remain capable of normal function. To address the capacity for adult-generated neurons to incorporate into functional circuits in the hyperglycemic DG, we measured Egr1 expression in granule cells (GCs), BrdU labeled four weeks prior, in Goto-Kakizaki (GK) rats, an established model of T2DM, and age-matched Wistars. The results indicate that while fewer GCs are generated in the DG of GK rats, GCs that survive readily express Egr1 in response to spatial information. These data demonstrate that adult-generated GCs in the hyperglycemic DG remain functionally competent and support neurogenesis as a viable therapeutic target.